2021
DOI: 10.1021/acs.jproteome.0c00848
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteome Profiling Revealed the Importance of mTOR Inhibition on CDK1 Activation to Further Regulate Cell Cycle Progression

Abstract: The mammalian target of rapamycin (mTOR) functions as a critical regulator of cell cycle progression. However, the underlying mechanism by which mTOR regulates cell cycle progression remains elusive. In this study, we used stable isotope labeling of amino acids in cell culture with a two-step strategy for phosphopeptide enrichment and high-throughput quantitative mass spectrometry to perform a global phosphoproteome analysis of mTOR inhibition by rapamycin. By monitoring the phosphoproteome alterations upon ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The inhibition of one signaling pathway may result in feedback activation of other signaling pathways. Blocking mTOR with rapamycin can cause CDK1 activation and further cell cycle progression [ 62 ]. Tumor development processes are complex, involving numerous signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of one signaling pathway may result in feedback activation of other signaling pathways. Blocking mTOR with rapamycin can cause CDK1 activation and further cell cycle progression [ 62 ]. Tumor development processes are complex, involving numerous signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…After entering the S phase, CDK1 participates in the regulation of DNA replication and centrosome replication and promotes mitosis. The high expression of CDK1 can increase the expression of the maturation-promoting factor complex and promote cells to enter the M phase from the G2/M phase ( Jin et al, 2021 ). This study showed that EPO could promote cell proliferation and CDK1 expression under hypoxia, but transfection of CDK1 interfering RNA eliminated the promoting effect of EPO on cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the sequencing results (KEGG pathway analysis identifies significantly enriched in PI3K-AKT signaling pathways and cell cycle signaling pathways.PI3K, IKKα and CDK1 were considered as significant differentially expressed and up-regulated, P-value <0.05,log2FC>0.5.) and some studies, PI3K, IKKα and CDK1 were associated with the ability of cells to proliferate (Fernandez-Majada et al, 2007;Tse et al, 2017;Li et al, 2019;Jin et al, 2021). At present, studies have investigated the effect of EPO on its transcription level under CoC1 2induced hypoxia, let alone the effect on the PI3K-IKKα-CDK1 signaling pathway.…”
Section: The Effect Of Epo On Cell Transcriptome Under Hypoxiamentioning
confidence: 99%
“…Previously, mTOR inhibition through rapamycin has demonstrated the role of this complex in the regulation of the cell cycle, notably via the degradation of cyclin D1 and upregulation of p27 KIP1 [ 92 , 93 ]. Additional later clues reinforce the importance of mTOR in cell-cycle regulation [ 94 , 95 , 96 ], indicating that autophagy is a potential determinant process modulating cell-cycle regulators. By regulating their availability, the autophagic program does not promote cell survival but enhances cell-cycle progression and may contribute to tumorigenesis.…”
Section: Autophagy Modulates Cell-cycle Regulatorsmentioning
confidence: 90%
“…The above-mentioned results suggest a strong reciprocal regulation between autophagy and cell-cycle regulators; perturbation of one leads to modulation of the other, as evidenced, for instance, by CDK4/6 or mTOR inhibitors. The importance of mTOR in cell-cycle regulation [ 94 , 95 , 96 ] reinforces the interest in using mTOR inhibitors in clinics as powerful anti-proliferative compounds, and for many cancer clinical trials as front-line therapy or alternative treatment to overcome resistance [ 115 ]. Unfortunately, faced with clinical data, either CDK4/6 or mTOR inhibitors are found to have clinical limitations as single agents in cancer therapy, as some patients develop clinical resistance.…”
Section: Therapeutic Interventions Combining Cell-cycle and Autophagy Modulatorsmentioning
confidence: 99%